Asthma Phenotypes and Biomarkers...61st Respiratory Care Journal Conference, June 19–21, 2024, Tampa, Florida. - Grunwell, Jocelyn R.; Fitzpatrick, Anne M. (Respiratory Care, 2025)
Asthma experienced by both adults and children is a phenotypically heterogeneous condition. Severe asthma, characterized by ongoing symptoms and airway inflammation despite high doses of inhaled and/or systemic corticosteroids, is the focus of research efforts to understand this underlying heterogeneity. Clinical phenotypes in both adult and pediatric asthma have been determined using supervised definition-driven classification and unsupervised data-driven clustering methods. Efforts to understand the underlying inflammatory patterns of severe asthma have led to the seminal discovery of type 2-high versus type 2-low phenotypes and to the development of biologics targeted at type 2-high inflammation to reduce the rates of severe asthma exacerbations. Type 2-high asthma is characterized by upregulation of T helper 2 immune pathways including interleukin (IL)-4, IL-5, and IL-13 along with eosinophilic airway inflammation, sometimes allergic sensitization, and responsiveness to treatment with corticosteroids. Type 2-low asthma is poorly responsive to corticosteroids and is not as well characterized as type 2-high asthma. Type 2-low asthma is limited by being defined as the absence of type 2-high inflammatory markers. Choosing a biologic for the treatment of severe asthma involves the evaluation of a panel of biomarkers such as blood eosinophils, total and specific immunoglobulin E/allergic sensitization, and fractional exhaled nitric oxide. In this review, we focus on the underlying pathobiology of adult and pediatric asthma, discuss the different phenotype-based treatment options for adult and pediatric type 2-high with or without allergic asthma and type 2-low asthma, and describe a clinical phenotyping approach to patients to guide out-patient therapy. Finally, we end with a discussion of whether pediatric asthma exacerbations necessitating admission to an ICU constitute their own high-risk phenotype and/or whether it is a part of other previously defined high-risk subgroups such as difficult-to-control asthma, exacerbation-prone asthma, and severe treatment-resistant asthma.